Consent for medical treatment of trans youth: a comparative analysis of the law in Australia and in England and Wales - Jowatt, S; Mathews, B; Herring, J (Monash University Publishing, 2024)
Clinical and legal regulation of consent to medical treatment for trans youth, both binary and non-binary, is complex as well as controversial. In this article, we outline the clinical context in which consent is sought for gender-affirming medical treatment of trans youth in Australia and in England and Wales. Then, informed by an understanding of the developing evidence base behind early gender-affirming treatment, the lived experience of trans young people, and a developmental approach to capacity in decision-making regarding medical treatment, this article goes on to consider the justifiability of current legal regulation in this area. First, this article examines general principles in relation to consent for children’s medical care, then charts the development of those principles through key cases that have shaped this particular area of law in Australia, England and Wales. These developments are then synthesised and compared in respect of the extent to which they promote or impede autonomous decision-making in the respective jurisdictions. We identify decisive similarities and differences between the jurisdictions, along with the likely practical implications for trans youth, their families, and treating doctors. Our analysis adds further weight to the growing consensus spanning the judiciary, doctors, legal scholars, and interest groups, that the law in Australia should be reformed to reduce unnecessary and harmful barriers to treatment for all trans youth.